Psychiatric Comorbidity Is Associated Prospectively with Diminished Opioid Analgesia and Increased Opioid Misuse in Patients with Chronic Low Back Pain. (October 2015) - Wasan, Ajay D.; Michna, Edward; Edwards, Robert R.; Katz, Jeffrey N.; Nedeljkovic, Srdjan S.; Dolman, Andrew J.; Janfaza, David; Isaac, Zach; Jamison, Robert N.
Abstract : Background: Opioids are frequently prescribed for chronic low back pain (CLBP), but there are little prospective data on which patient subgroups may benefit. Psychiatric comorbidity, such as high levels of depression and anxiety symptoms (termed comorbid negative affect [NA]), is a common presentation and may predict diminished opioid analgesia and/or increased opioid misuse. Methods: The authors conducted a 6½-month prospective cohort study of oral opioid therapy, with an active drug/placebo run-in period, in 81 CLBP patients with low, moderate, and high levels of NA. Treatment included an opioid titration phase with a prescribing physician blinded to NA group assignment and a 4-month continuation phase, during which subjects recorded daily pain levels using an electronic diary. The primary outcome was the percent improvement in average daily pain, summarized weekly. Results: There was an overall 25% dropout rate. Despite the high NA group being prescribed a higher average daily dose of morphine equivalents, linear mixed model analysis revealed that the 24 study completers in each of the high NA and low NA groups had an average 21 versus 39% improvement in pain, respectively ( P < 0.01). The high NA group also had a significantly greater rate of opioid misuse (39 vs . 8%, P < 0.05) and significantly more and intense opioid side effects ( P < 0.01). Conclusions: These results indicate that the benefit and risk considerations in CLBP patients with high NA versus low NA are distinctly different. Thus, NA is an important phenotypic variable to characterize at baseline, before deciding whether to prescribe opioids for CLBP. Abstract : In 81 patients with chronic low back pain prospectively studied for 6½ months with placebo followed by opioids, those with high negative affect were prescribed larger average daily doses of opioids, had less improvement in pain, and had a greater rate of opioid misuse than those with low negative affect. These prospective data support previous cross-sectional data to suggest that negative affect presents an important risk factor in inadequate analgesia from opioids and opioid misuse.